2012
DOI: 10.1021/ic300852t
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium(II) Complex Formation with Selenourea and Thiourea in Solution: An XAS and 113Cd NMR Study

Abstract: The complexes formed in methanol solutions of Cd(CF3SO3)2 with selenourea (SeU) or thiourea (TU), for thiourea also in aqueous solution, were studied by combining 113Cd NMR and X-ray absorption spectroscopy. At low temperature (~200 K) distinct 113Cd NMR signals were observed, corresponding to CdLn2+ species (n = 0 - 4, L = TU or SeU) in slow ligand exchange. Peak integrals were used to obtain the speciation in the methanol solutions, allowing stability constants to be estimated. For cadmium(II) complexes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 84 publications
1
16
0
1
Order By: Relevance
“…It indicated that H A and H C were most likely to be coordination sites in the third stage because the signals of C A and C C were shielded. 35 …”
Section: Resultsmentioning
confidence: 99%
“…It indicated that H A and H C were most likely to be coordination sites in the third stage because the signals of C A and C C were shielded. 35 …”
Section: Resultsmentioning
confidence: 99%
“…For example, the average crystallographic Cd-S bond distances for [Cd(thiourea) 4 ](NO 3 ) 2 is 2.560 Å, while the mean Cd-S bond length from Cd K-edge EXAFS spectroscopy is 2.53 ± 0.02 Å. 78 …”
Section: Resultsmentioning
confidence: 99%
“…Cd II has serious effects on human health, causing damage to kidneys and lungs, and triggers bone diseases and potentially leads to cancer. [23][24][25][26] The structural similarity of Cd 2+ to Zn 2+ has prompted thorough comparisons of the coordination properties of the two ions and studies of the metal selectivity for Zn 2+ , for example, in mammalian metal transporters, such as zinc influx transporters. [21,22] This has led to further research focusing on the development of chelating agents to prevent the uptake of Cd II by cells.…”
mentioning
confidence: 99%